Study on the Vehicle Linear Dynamic Interval in a Traffic Flow - Fyodorovich Danilov, Oleg; Ivanovich Kolesov, Victor; Alexandrovich Sorokin, Denis; Leonidovich Gulaev, Maxim (Communications - Scientific Letters of the University of Zilina, 2021)
The transportation industry of a modern city involves the effective systems for the road traffic management. To manage any object is impossible without understanding its specifics. The tasks of road traffic management are based on mathematical models of traffic flows. The ``following the leader'' model based on the linear dynamic interval of vehicles has become widely accepted in the model analysis. The paper discusses the mathematical model of the linear dynamic interval of vehicles; the model is identified structurally and parametrically. Coefficients of the model are analyzed in detail; a generalized assessment of the dynamic performance of the traffic flow, evolved in various road conditions, is given. The study has resulted in the proposed basic models for traffic flows that can be used for algorithmic support of the model analysis of traffic flows and the road traffic management.
Keywords: smart city; dynamic interval; traffic flow; speed; intensity; density; road coverage